2021
DOI: 10.1007/jhep04(2021)015
|View full text |Cite
|
Sign up to set email alerts
|

Probing electroweak phase transition with multi-TeV muon colliders and gravitational waves

Abstract: We study the complementarity of the proposed multi-TeV muon colliders and the near-future gravitational wave (GW) detectors to the first order electroweak phase transition (FOEWPT), taking the real scalar extended Standard Model as the representative model. A detailed collider simulation shows the FOEWPT parameter space can be greatly probed via the vector boson fusion production of the singlet, and its subsequent decay to the di-Higgs or di-boson channels. Especially, almost all the parameter space yielding d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 104 publications
0
35
0
Order By: Relevance
“…It has also been shown that a MuC can discover the new physics behind the (g − 2) µ anomaly [50][51][52][53], assuming that the current running experiments at Fermilab [54] and JPARC [55] establish the (g − 2) µ excess as a source of new physics. In addition to these motivations, the reach of a multi-TeV MuC has recently been studied in the context of a few BSM scenarios [56][57][58][59]. Here we add another important motivation, namely we show that such a MuC can be able to cover thermal DM [60] beyond the capabilities of its main competitor, a putative high energy proton-proton collider [61,62].…”
Section: Jhep06(2021)133mentioning
confidence: 93%
“…It has also been shown that a MuC can discover the new physics behind the (g − 2) µ anomaly [50][51][52][53], assuming that the current running experiments at Fermilab [54] and JPARC [55] establish the (g − 2) µ excess as a source of new physics. In addition to these motivations, the reach of a multi-TeV MuC has recently been studied in the context of a few BSM scenarios [56][57][58][59]. Here we add another important motivation, namely we show that such a MuC can be able to cover thermal DM [60] beyond the capabilities of its main competitor, a putative high energy proton-proton collider [61,62].…”
Section: Jhep06(2021)133mentioning
confidence: 93%
“…The singlet extended SM, known as "xSM", consists of the standard SM Higgs doublet H T = G + , v EW + h + iG 0 / √ and a real gauge singlet S = v s +s where the electroweak vacuum is (v EW , v s ) [28,38,[116][117][118][119][120][121][122]. The tree level potential in this setup is defined as…”
Section: Xsmmentioning
confidence: 99%
“…Thanks to the technological development [21], a renewed idea that has recently gathered much momentum is the option of a high-energy muon collider that could reach the multi-(tens of) TeV regime with very high luminosity [22][23][24]. It has been demonstrated in the recent literature that a highenergy muon collider has great potential for new physics searches at the energy frontier from direct µ + µ − annihilation and a broad reach for new physics from the rich partonic channels [25][26][27][28][29], as well as precision measurements for SM physics [30] and beyond [31][32][33][34][35][36][37][38][39]. Of particular importance is the connection between the muon collider expectation and the tantalizing hint for new physics from the muon g − 2 measurement [40,41].…”
Section: Jhep12(2021)162mentioning
confidence: 99%